Geographical Distribution of Egyptian Lot-Chosen and Civil Associations’ Pilgrims - Chronic Diseases and their Demographic Characteristics - Samak, Yasser Abdelazim Abdelmawgoud (International Journal of Geography and Geology, 2016)
This study examines modes of transport for Egyptian lot-chosen and civil associations’ pilgrims and their demographic characteristics in the period starting from 2000 in terms of increase in their number and their modes of transport (Air – Land – Sea). Analysis of Variance (ANOVA) is used to test the differences between pilgrims across various demographic variables and modes of transportations across censuses and Least Square Difference (LSD) test was applied. Maps and scatters are also plotted. By studying the statistical differences between pilgrims in terms of gender, it was found that there was no difference reported by census among the female pilgrims throughout the study period while records of governorates found differences among females. All characteristics revealed the presence of significant differences when applied to the pilgrims’ governorates of origin. Till date land travel is more encouraged than sea or air. Hence there is an urgent need to improve land transport and make it more luxurious and convenient for different economic classes.